Influence of the epitaxial composition on N-face GaN KOH etch kinetics determined by ICP-OES - Tautz, Markus; Kuchenbrod, Maren T.; Hertkorn, Joachim; Weinberger, Robert; Welzel, Martin; Pfitzner, Arno; Díaz Díaz, David (Beilstein Journal of Nanotechnology, 2020)
Roughening by anisotropic etching of N-face gallium nitride is the key aspect in today’s production of blue and white light emitting diodes (LEDs). Both surface area and number of surface angles are increased, facilitating light outcoupling from the LED chip. The structure of a GaN layer stack grown by metal organic chemical vapour deposition (MOCVD) was varied in the unintentionally doped u-GaN bulk region. Different sequences of 2D and 3D grown layers led to a variation in dislocation density, which was monitored by photoluminescence microscopy (PLM) and X-ray diffraction (XRD). Thin-film processing including laser lift off (LLO) was applied. The influence of epitaxial changes on the N-face etch kinetics was determined in aqueous KOH solution at elevated temperature. Inductively-coupled plasma optical emission spectroscopy (ICP-OES) was used to measure the etch progress in small time increments with high precision. Thereby, the disadvantages of other techniques such as determination of weight loss or height difference were overcome, achieving high accuracy and reproducibility.
Keywords: etching; GaN; ICP-OES; KOH; LED